Young People’s Perception of the Danger of Risky Online Activities: Behaviours, Emotions and Attitudes Associated with Their Digital Vulnerability - Sonia Carcelén-García; Mónica Díaz-Bustamante Ventisca; María Galmes-Cerezo (Social Sciences, 2023)
Digital leisure has become the main reason young people make use of the Internet and social media. Previous research shows the danger of certain activities in the online environment. Of particular concern are those of a recreational nature, which are more socially accepted by young people; among them one can find: online gambling and betting, online shopping and eGames, and the consumption of content on social media. This study aims to identify the behavioural and psychographic variables which impact the probability that young people will perceive the danger of these risky activities. We have carried out a descriptive and causal investigation with non-experimental cross-cutting analysis through a computer-assisted phone survey on a sample of 1500 young people aged between 18 and 35. The results show that all the activities are perceived as dangerous by the majority of those questioned, but a large percentage of young people do not perceive any risk in online gambling, betting and eGames. We have determined several psychographic and behavioural variables to help predict the perception of risk among young people to help define formal and informal policies for reducing their vulnerability in the event of the inappropriate use of the studied activities.